Extracellular vesicles in leukemia. (January 2018) - Pando, Alejandro; Reagan, John L.; Quesenberry, Peter; Fast, Loren D.
Highlights: Comprehensive Review of Leukemia extracellular vesicles. Leukemia extracellular vesicle characterization. Leukemic extracellular vesicles alter their microenvironment. Cancer extracellular vesicles act as immunomodulators. Extracellular vesicle clinical, diagnostic, and therapeutic potential. Abstract: Extracellular vesicles (EV) are nano-sized membrane enclosed vehicles that are involved in cell-to-cell communication and carry cargo that is representative of the parent cell. Recent studies have highlighted the significant roles leukemia EVs play in tumor progression, and ways in which they can lead to treatment evasion, thus meriting further investigation. Leukemia EVs are involved in crosstalk between the leukemia cell and its surroundings, transforming it into a cancer favorable microenvironment. Due to the diverse biological content found in leukemia EVs, they have an assortment of effects on the cells they interact with and can be harnessed as candidates for diagnostic and therapeutic treatments. This review focuses on EVs in the context of leukemia and the means by which they modulate their microenvironment, hematopoiesis, and the immune system to facilitate malignancy. We will also address current and prospective EV-based therapeutics.